Impact of shift work on sleep and fatigue in Maritime pilots. Issue 7 (3rd July 2021) - Tait, Jamie L.; Chambers, Timothy P.; Tait, Regan S.; Main, Luana C.
Abstract: This study examined how objective measures of sleep change across shift-cycles, and the impact of this on sleep quality and fatigue. Forty maritime pilots were recruited from Australian ports. Sleep wake-behaviour (timing and length), and self-reported sleep quality and fatigue, were assessed to determine any impact of roster status and 'on-call' status. On-roster pilots experienced reduced night time sleep duration compared to those off-roster (57 ± 8.8 min), while working on-call also diminished night time sleep duration (126 ± 11.3 min) and quality, compared to workers not on-call. Fatigue scores indicated that participants were not fully recovered prior to commencing rostered night shift, while sleep quality was significantly worse following sleep that occurred after a night shift, compared to after a day shift. These findings potentially support workplace negotiations to change future shift cycles, and to adopt monitoring systems that may mitigate the risk of fatigue-related accidents and chronic health outcomes. Practitioner summary: Long and irregular work hours of maritime pilotage can compromise worker performance and safety. This observational study found that on-roster pilots experience reduced sleep duration compared to those off-roster, while working on-call further diminishes sleep duration and quality. Future workload/fatigue monitoring systems may mitigate fatigue-related accidents and adverse chronic health outcomes. Abbreviations: ANOVA: analysis of variance; ANCOVA: analysis of covariance; BMI: body mass index; CVD: cardiovascular disease; h: hours; mins: minutes; SE: standard error of the mean; SD: standard deviation; SO: sleep opportunities; TST: total sleep time; WASO: wake after sleep onset